Development of a combined diphtheria vaccine based on diphtheria anatoxin with microbial adjuvant in the light of modern strategies of vaccines development - Yelyseyeva, I; Babich, Ye; Zhdamarova, L; Bilozersky, V; Kolpak, S (Annals of Mechnikov's Institute, 2020)
The review article is devoted to the consideration of approaches to the practical implementation of the main provisions of modern ideas about the role and mechanisms of innate immunity for the development of vaccines. Initiation of the body's immune defenses occurs through the recognition of microbial pathogens using typical molecular structures associated with pathogens (PAMPs), mediated by image recognition receptors (PRRs), which are expressed by cells of the innate immune system. Тhe so-called Toll-like receptors (TLR) play a central role in initiating immune responses. Other PRRs such as membrane-bound lectin C receptors (CLR), cytosolic proteins such as the nucleotide-binding oligomerization domain - NOD-like receptors (NLR) and RIG-I-like are involved in the recognition of PAMP and the control of innate immunity. receptors (RLR), AIM-2-like receptors, and a family of enzymes that function as intracellular nucleic acid sensors, including OAS and cGAS proteins also involved in the recognition of PAMP and control of innate immunity. Innate control of adaptive immunity is now an established paradigm. PRR determines the origin of antigens recognized by receptors expressed on T cells and B cells, as well as determine the type of infection with which collides with the body, and teaches lymphocytes to induce an appropriate effector class of the immune response. A modern branch of vaccinology is a new paradigm for the development of broad-spectrum prophylactic drugs based on trained immunity (TIbV). These are vaccines that induce the learning or training of innate immune cells, the essence of which lies in their long-term metabolic and epigenetic changes, which lead to an enhanced cellular response to the second antigenic stimulus by the same or unrelated specific microbial stimulus. Because trained immunity is typically triggered by PRRs, TIbV must be formed from microbial structures containing the appropriate PRR ligands, namely, PAMPs. Unlike conventional vaccines, which aim to obtain only specific responses to vaccine-associated antigens, TIbV aims to stimulate a wider range of reactions. Broad protection can be achieved by enhancing the nonspecific effector response of innate immune cells to pathogens and using the dendritic cells activation state to enhance the adaptation of the T cell response to both specific and unrelated antigens. The concept of TIbV is in its infancy, but a number of modern anti-infective vaccines, immunomodulators and vaccine adjuvants can already be considered from the standpoint of the TIbV category. Induction can be achieved in various ways that enhance immunity, which can be involved by bacteria, fungi (β-glucan) or metabolic "trainers", as well as some cytokines. A new paradigm for drug development and therapeutic interventions for the prevention and treatment of infectious diseases is also the defeat of bacterial virulence as an alternative to antimicrobial therapy. One of the many antivirulence targets is adhesion. If it is possible to suppress adhesion, accordingly, it is possible to suppress the corresponding infection. This approach forms the basis of anti-adhesive strategies that have been invented to prevent various bacterial infections. Thus, the development of vaccines that prevent the initial stage of infection is in line with the anti-adhesive strategy. A combined diphtheria vaccine based on native purified diphtheria toxoid (NODA) with an adjuvant of microbial origin is developed at the SI “IMI NAMN” at the stage of preclinical trials. As an adjuvant in the candidate vaccine, a preparation of C.diphtheriae, var.gravis, tox + native surface antigens is used, which have not undergone modification or even denaturation with chemicals and therefore contain molecular structures as similar as possible to natural PAMPs and provide targeted antigen stimulation of cells of the innate immune system, obtained by physical means of disintegration of microbial cells (ultrasound or electromagnetic radiation of extremely high frequency). Studies have shown that the nativeness of antigenic candidate drugs for adjuvants is a key element of their effectiveness. Experimental samples of diphtheria bacterial surface antigens have shown themselves as adjuvant for diphtheria toxoid, capable of replacing neurotoxic aluminum hydroxide, and immunomodulator, which increase phagocytic activity in the first and repeated antigenic stimuli, and also promote the release of nasopharyngeal mucosa of rabbits vaccinated with experimental samples of the combined diphtheria vaccine and infected with a culture of C. diphtheriae. The formation of an immunologically strong mucosal barrier is considered to be an effective strategy to prevent infection at the point of contact between microbes and the host. However, modern standards of vaccine technology usually apply only to pathogens that have already crossed the mucosal barrier. In contrast to licensed vaccines, vaccination on mucosal surfaces, including the oral route of administration of the vaccine, can successfully stimulate the humoral and cellular immune response in both systemic and mucosal areas of the entrance gate of infection to establish a broader and longer-lasting protection. Experimental samples of the combined diphtheria vaccine with bacterial adjuvant were tested using the oral route of administration of the vaccine in combined vaccination regimens, and, as the results of experiments showed, the adjuvant and phagocytosis stimulating effect of the studied candidate vaccines was maintained. The obtained data demonstrated the prospect of widespread use of oral immunization as the most natural, physically and psychologically painless way to administer vaccines both for emergencies in the diphtheria outbreak and to maintain collective diphtheria immunity by booster immunization. However, oral delivery is a complex task that requires a special composition to overcome harsh gastrointestinal environments and avoid the induction of tolerance to achieve effective protection, which requires detailed justification of oral vaccines, including key biological and physicochemical aspects of next-generation oral vaccines. Another way to increase the safety of diphtheria vaccines during repeated vaccinations, which opens up prospects for specific immune protection of persons with allergic reactions, was the experimental application of the principles of specific immunotherapy in vaccinations of experimental animals. The obtained results indicate that the previous oral administration of antigenic drugs C. diphtheriae prevented the development of allergic skin reactions in experimental rabbits with subsequent subcutaneous administration of diphtheria vaccines. Studies on the development of a combined diphtheria vaccine with an adjuvant of bacterial origin convincingly showed the immunogenicity of the obtained experimental samples of the candidate vaccine and the possibility of combining the efficacy and safety of the drug at a certain dosage and degree of purification of antigenic drug. But for further research, it will be essential to expand knowledge about the sensitive pathways of the innate immune system and to determine the rules of interaction that determine the functions of these pathways in the context of diphtheria infection. Special attention should be paid to the study of the protective effect of the drug, the study of patterns of formation of antibacterial diphtheria immunity and the determination of optimal ratios of NODA and bacterial antigen in the vaccine. DOI: 10.5281/zenodo.3885130